Data quality guarantee for credible caching device selection in mobile crowdsensing systems - Zhao,C; Yang,S; Yan,P; Yang,Q; Yang,X; McCann,J (IEEE Wireless Communications, 2018)
CrowdsensingSystems(MCSs)present a flexible and economical alternative to traditionalinfrastructure based large-scale sensing through therecruitment of personal mobile devices as data sources.As this becomes a popular sensing approach it will impactthe capacity of typical centralized cellular communicationinfrastructures widely adopted by MCS applicationsand any costs accrued. Following the trend towardsedge processing, Mobile Edge Caching offloads data andservices from the system core to reduce service latency andbandwidth occupation. However, in the MCS case the edgedevice is owned by the general public and are thereforemore vulnerable to data or calculation manipulation bythe user. We now better understand sensor data anduser trustworthiness but have no way to determine whichof devices could also be trusted, i.e. act as a crediblecaching device. In this article, we treat the quality ofsensing data reported by each user as an indication oftheir possibility of providing credible caching services.Specifically, we conduct a comprehensive study of the dataquality problem with regards to cache-enabled MCSs, anddevelop an incentivization method to encourage users toactively provide high quality data. That is, quality-awarebehavior evaluation is core to the credible caching deviceselection process. Results of extensive simulations basedon real-world data verify the effectiveness of our design.We also highlight several promising research directionsthat remain open for further elaborations.